2013
DOI: 10.1111/and.12139
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of carcinomain situin testicular biopsies of infertile Iranian men

Abstract: Almost all testicular germ cell tumours are proved to originate from carcinoma in situ cells. Infertility is one of the factors that increase the risk of carcinoma in situ. The reported prevalence for carcinoma in situ from different parts of the world is 0-3.7% in infertile men. This retrospective study was performed to determine the prevalence of carcinoma in situ in Iranian infertile men. We reviewed the testicular biopsies of 1153 infertile men at the pathology department of Avicenna Infertility Center. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A study of 100 biopsies at the time of adult orchidopexy found no instances of malignancy 3 . Smaller series involving adult cryptorchid men report rates of GCNIS ranging from 2% to 23% 15,43,44 . Incidental GCNIS was seldom reported in our review and not addressed by our analysis, but in light of available literature, routine tissue sampling in men considering orchidopexy for improved fertility may afford a risk that outweighs the potential benefit.…”
Section: Discussionmentioning
confidence: 67%
“…A study of 100 biopsies at the time of adult orchidopexy found no instances of malignancy 3 . Smaller series involving adult cryptorchid men report rates of GCNIS ranging from 2% to 23% 15,43,44 . Incidental GCNIS was seldom reported in our review and not addressed by our analysis, but in light of available literature, routine tissue sampling in men considering orchidopexy for improved fertility may afford a risk that outweighs the potential benefit.…”
Section: Discussionmentioning
confidence: 67%
“…All testes with later ITGCN were originally intraabdominally placed. 12 ITGCN was found in 0 to 8% in other studies on follow-up testicular biopsies from adult men having previous prepubertal orchiopexy because of cryptorchidism. 9,13,14 In contrast, ITGCN is found more rarely in series with prepubertal cryptorchid testes.…”
Section: Introductionmentioning
confidence: 75%
“…8,9 ITGCN is demonstrated in 2.0 to 3.2% of cryptorchid testis from young men who were not treated in childhood. 10,11 Recently, Soltanghoraee et al 12 found ITGCN in 1.7% of 182 men with testes biopsied because of infertility, and all with previous orchiopexy because of cryptorchidism. All testes with later ITGCN were originally intraabdominally placed.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical staining was not used in that study, which may explain why they did not diagnose any ITGCN case at all. Soltanghoraee et al 35 reviewed testicular biopsies of 1,153 infertile men. One hundred and ninety patients had a history of unilateral or bilateral cryptorchidism, 127 had undergone orchidopexy (the age of orchidopexy was known only in 95 patients (between 4-48 years of age).…”
Section: Malignancymentioning
confidence: 99%